ESTABLISHMENT OF AN EFFICIENT MICROPROPAGATION PROTOCOLS FOR THREE KENAF (HIBISCUS CANNABINUS L.) CULTIVARS - A.M. Ibrahim,; E. J. Aldabbagh,; A. R. Abbas,; F. Kayat, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to establish an efficient micropropagation protocol for three popular kenaf (Hibiscus cannabinus L.) cultivars (V36, HF992 and KB6) using different types of plant growth regulators (PGR’s) on Murashige and Skoog medium (MS). The shoot tip, cotyledon and hypocotyl isolated from 2 weeks old seedlings were used as explants. MS medium fortified with different types and concentrations of cytokinins and auxin were evaluated for establishment callus formation, shoot multiplication and rooting. Among different PGR’s used, 5.0 mg/l 2iP + 0.1 mg/l NAA was the best concentration for direct shoot regeneration from cotyledon with shooting percentage of 55% in HF992 cultivar. In multiple shoot induction experiment, 1.0 mg/l TDZ + 0.1 mg/l NAA mg/l concentration has induced the highest (10.4) shoots/explant. Moreover, indirect shoot regeneration was established from callus which was induced from cotyledon, maximum callus induction percentage (88.75%) was recorded on 0.5 mg/l TDZ and 1.0 mg/l NAA in V36 variety. While, for shoot elongation and rooting, MS media half strength supplemented with 1.0 mg/l kinetin + 1.0 mg/l IBA was found to be an optimum concentration.